PERAN DAN KONTRIBUSI CURAHAN WAKTU KERJA WANITA PADA USAHA PEMBESARAN IKAN PATIN (Pangasius sp) DALAM KOLAM (Studi Kasus Di Desa Pudak Kecamatan Kumpeh Ulu Kabupaten Muaro Jambi) - Asmaida Asmaida; Rogayah Rogayah (Jurnal MeA (Media Agribisnis), 2020)
Research was carried out in Pudak Kumpeh Ulu village, Muaro Jambi District. Its  goal was 1). Describing the female's role in the pond's catfish  farming. 2). To Calculate  amount of working duration of  female and male in   catfish   farming in a pond. 3). Analyzing the contributions of female's working duration on  a catfish farming in a ponds. The research method   used a survey method. It also used a primary and secondary data, with cross section data type based on ratio scale measurement. The population were   amount of housewife who did an  fish enlargement of the catfish farming in a pond. There were 33 Samples  that  chosen randomly ones. The descriptive analysis method was used in this research.  The results showed that : 1). The role of female on the catfish farming in the pond  showed high enough category, females were almost completely involved in pond preparation activities (drying ponds, weaning, fertilization and water giving), seed spreading, feeding, pond-  cleaning, and harvesting. 2). The everage  of female's work duration on   the catfish farming in the pond e.g.  31.48 hours/period in the pool preparation activities (pool drying, sowing, fertilization and water giving), 4.12 hours/period in seed spread, 338.18 hours/period for feeding, 30.91 hours/period in  pool-  cleaning, and harvesting for 3.36 hours/period. 3). It was  91.17% contribution of female's work duration on  the catfish farming in the pond  and the remaining as men work duration was 8.83%